The Lima Reader History, Culture, Politics - Aguirre, Carlos; Walker, Charles F. (The Latin America Readers, 2017)
Covering more than 500 years of history, culture, and politics, The Lima Reader seeks to capture the many worlds and many peoples of Peru's capital city, featuring a selection of primary sources that consider the social tensions and cultural heritages of the "City of Kings."